Effect of Flying at High Altitude on Early Exposure of Paracetamol in Humans - Idkaidek, Nasir; Al-Ghazawi, Ahmad (Drug Research, 2019)
Pharmacokinetics of paracetamol (APAP) was studied on-board during an air flight and compared to those on ground after 500 mg oral dose in 20 healthy human volunteer in parallel design study. Saliva samples were obtained every 15 min up to 2 h after dosing. Pharmacokinetic parameters were calculated by non compartmental analysis and one compartment models using Winnonlin program V5.2. Results have showed that on-board to ground ratios for area under curves AUC0→1, AUC0→2, time to reach maximum saliva concentration Tmax, absorption rate constant Ka and maximum saliva concentration Cmax were 0.62, 0.38, 1.01, 0.81 and 0.79 respectively. Effective membrane permeability coefficients were optimized by Nelder-Mead algorithm using Simcyp program V13. This showed similar rate of absorption and early exposure up to one hour, and lower bioavailability after 1 h on-board. This can be explained by the increased liver blood flow at high altitude that led to increased liver metabolism on-board. However, APAP elimination parameters were not calculated due to short sampling time. This suggests a need for dose adjustment on-board during long air flights, especially for narrow therapeutic index drugs with flow limited metabolism.
Keywords: high altitude; paracetamol; early exposure; saliva sampling